Between fire and custom: A study of Indian cremation practices on the Island of the Gods (Bali) - Nandmehar, Sarita; Wardana, I Ketut; Wariati, Ni Luh Gede (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background: Cremation tradition is one of the ritual practices that has deep meaning in Indian and Balinese culture. This study explores the cremation practices of Indians on the island of Bali, which reflect the intersection between their ancestral traditions and local Balinese customs. In the context of globalization and migration, this study is relevant to understanding the dynamics of cultural interaction and the sustainability of ritual identity in a multicultural society. This research aims to analyze how Indians in Bali carry out their cremation practices, adapting or maintaining traditional Indian elements within the framework of Balinese customs. Methods: The methodology used is qualitative with in-depth interview techniques, participatory observation, and document analysis. Data was collected from the Indian community living in Bali, Balinese traditional leaders, and religious leaders. Findings: The results show that the cremation practices of Indians in Bali are the result of a process of cultural adaptation and negotiation. Although the core rituals continue to reflect Indian traditions, many elements are integrated with Balinese customs, such as the use of cremation sites and the involvement of local communities. This outcome reflects a unique cultural harmony and the sustainability of the tradition amidst the dynamics of social change. Conclusions: This study concludes that the cremation practice of Indians in Bali serves not only as a spiritual ritual but also as a symbol of harmonious cultural interaction. Novelty/Originality of this article: The findings have important implications for cultural anthropology and intercultural studies and can serve as a reference in designing policies that support cultural diversity in a globalized society.